METHODOLOGY OF ORGANIZING FOLKLORE ENSEMBLES IN EDUCATIONAL INSTITUTIONS - Gulliyeva Yulduzxon Yuldoshovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article describes a number of scientific considerations on the organization of folklore ensembles in educational institutions and improving the effectiveness of the work of such ensembles.